2018
DOI: 10.1021/acs.est.8b04056
|View full text |Cite
|
Sign up to set email alerts
|

Consensus Modeling of Median Chemical Intake for the U.S. Population Based on Predictions of Exposure Pathways

Abstract: Prioritizing the potential risk posed to human health by chemicals requires tools that can estimate exposure from limited information. In this study, chemical structure and physicochemical properties were used to predict the probability that a chemical might be associated with any of four exposure pathways leading from sources-consumer (near-field), dietary, far-field industrial, and far-field pesticide-to the general population. The balanced accuracies of these source-based *

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
116
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 93 publications
(133 citation statements)
references
References 94 publications
(186 reference statements)
3
116
0
Order By: Relevance
“…A comparison of the SHEDS values with biomonitoring data in Biryol et al (2017) demonstrated that the SHEDS-HT values were likely over-estimates by at least two orders of magnitude. Recent work has integrated multiple SHEDS models (as well as other mechanistic exposure models) with NHANES biomonitoring data in an evaluation framework called the Systematic Empirical Evaluation of Models (SEEM)( Ring et al, 2019 ). These efforts will allow for the integration of food contact pathways into next-generation ExpoCast exposure values while simultaneously correcting over-conservative models for individual pathways.…”
Section: Discussionmentioning
confidence: 99%
“…A comparison of the SHEDS values with biomonitoring data in Biryol et al (2017) demonstrated that the SHEDS-HT values were likely over-estimates by at least two orders of magnitude. Recent work has integrated multiple SHEDS models (as well as other mechanistic exposure models) with NHANES biomonitoring data in an evaluation framework called the Systematic Empirical Evaluation of Models (SEEM)( Ring et al, 2019 ). These efforts will allow for the integration of food contact pathways into next-generation ExpoCast exposure values while simultaneously correcting over-conservative models for individual pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Related emerging topics are the 'exposome' concept [44,45] or 'safe-by-design' initiatives [46]. Underlying exposure data generation increasingly builds on highthroughput and spatial methods [47][48][49][50][51], and harmonized biomonitoring efforts [43,52], which will influence the availability, quality and complexity of exposure information. Various important achievements including exposomics, intake fraction modelling, and personal exposure sampling are further detailed elsewhere (e.g.…”
Section: Considering Major Scientific Trendsmentioning
confidence: 99%
“…These data may be used to prioritize chemicals for a database. For example EPA's modeling predicted 1880 chemicals would have median population exposures above 0.1 mg/kg-day [27]. Chemical databases should also be developed that feature chemicals shown to be active in breast cancer-related pathways, such as estrogen receptor activation or DNA Data resources that are now available from the US Environmental Protection Agency (EPA) and other sources provide valuable information to help build environmental chemical databases that are relevant to breast cancer.…”
Section: Capturing Molecular Information Using Omicsmentioning
confidence: 99%
“…These data may be used to prioritize chemicals for a database. For example EPA's modeling predicted 1880 chemicals would have median population exposures above 0.1 mg/kg-day [27]. Chemical databases should also be developed that feature chemicals shown to be active in breast cancer-related pathways, such as estrogen receptor activation or DNA damage.…”
Section: Capturing Molecular Information Using Omicsmentioning
confidence: 99%